2000
DOI: 10.1038/sj.bmt.1702402
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF reduces IFN-γ and IL-4 production by T cells after allogeneic stimulation by indirectly modulating monocyte function

Abstract: Summary:Despite a 10-fold increase of T cell dose, the incidence and severity of acute GVHD following allogeneic transplantation of G-CSF-mobilized PBSC is not increased compared to BMT. Experimental murine studies demonstrate that G-CSF polarizes donor T cells toward a type 2 cytokine response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
2
37
1
Order By: Relevance
“…Experimental murine studies demonstrate that G-CSF polarizes donor T cells toward a type 2 cytokine response. 15 Recently, we have measured the concentration of several cytokines in the serum of patients after allogeneic hematopoietic stem cell transplantation, including soluble interleukin-2 receptor (sIL-2R), IL-6, IL-8 and tumor necrosis factor-a (TNF-a). Results showed that sIL-2R levels increased during aGVHD and that the increase of sIL-2R levels in serum preceded the clinical signs of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental murine studies demonstrate that G-CSF polarizes donor T cells toward a type 2 cytokine response. 15 Recently, we have measured the concentration of several cytokines in the serum of patients after allogeneic hematopoietic stem cell transplantation, including soluble interleukin-2 receptor (sIL-2R), IL-6, IL-8 and tumor necrosis factor-a (TNF-a). Results showed that sIL-2R levels increased during aGVHD and that the increase of sIL-2R levels in serum preceded the clinical signs of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…One non-G-CSF-treated patient died before engraftment because of invasive fungal infection. The median time to reach neutrophil engraftment (40.5 Â 10 9 /l) was 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) days in G-CSF-treated patients and 17 days in untreated ones (Po0.001). No significant effect was found on the day of platelet engraftment between the two groups, 18 (10-200) days vs 20 (10-89) days, respectively.…”
Section: Haematological Recovery and Transfusionsmentioning
confidence: 99%
“…[11][12][13][14][15][16] G-CSF also polarises T cells to produce type-2 cytokines, which may be associated with reduced severity of acute GVHD. [17][18][19][20] We carried out a retrospective trial to evaluate the effect of G-CSF on GVHD and other parameters in patients undergoing HSCT with HLA-identical sibling donors.…”
mentioning
confidence: 99%
“…6,7 In vitro human studies have demonstrated that PBSC products have high levels of T cell inhibitory activity. [8][9][10][11][12][13] This effect has been variously attributed to the high levels of IL-10 produced by monocytes, 14 to modulation of monocyte function, 15 and more recently, to a mobilisation-associated increase in certain dendritic cell (DC) subsets. 16,17 DC constitute a system of antigen-presenting cells that play a critical role in regulating immune responses.…”
mentioning
confidence: 99%